ASYMMETRIC CARRIERS: SHIPPING TO HETEROGENEOUS CUSTOMERS UNDER PERSONALIZED PRICING - Faqi, Xie (PEOPLE: International Journal of Social Sciences, 2024)
Problem definition: We study two asymmetric information carriers that adopt personalized pricing to provide transportation services to end-market consumers. Consumers are heterogeneous in their sensitivity to the quality of the product arriving at their destination. Academic/practical relevance: Consumer dissatisfaction with personalized pricing and product quality may cause them to turn to competitors to satisfy their needs. Competition among carriers and information sharing strategies have the potential to transform carriers’ decisions and thus retain consumers. Methodology: We develop a two-period game model to capture carriers’ freight rates (personalized and non-personalized pricing) and information sharing decisions. Results: We find that market competition and quality-sensitivity information sharing do not affect the incumbent carrier’s personalized pricing but moderate the extent of it by the entrant carrier. In equilibrium, the high-type incumbent carrier can benefit from information sharing, but the high-type entrant carrier may suffer. We also find that a more competitive market may increase the incumbent carrier’s total profit and may decrease the total profit of the entrant carrier. Managerial implications: Our research provides guidance on carriers’ personalized pricing and whether a new entrant should strive to become the market leader. At the same time, our research also provides guidance on whether the informed carrier should share its strategic information.